Chicken speckle-type POZ protein (SPOP) negatively regulates MyD88/NF-κB signaling pathway mediated proinflammatory cytokine production to promote the replication of Newcastle disease virus - Zhongming Meng; Yanbi Wang; Xianya Kong; Mona Cen; Zhiqiang Duan (Poultry Science, 2024)
ABSTRACT: The speckle-type POZ protein (SPOP) is demonstrated to be a specific adaptor of the cullin-RING-based E3 ubiquitin ligase complex that participates in multiple cellular processes. Up to now, SPOP involved in inflammatory response has attracted more attention, but the association of SPOP with animal virus infection is scarcely reported. In this study, chicken MyD88 (chMyD88), an innate immunity-associated protein, was screened to be an interacting partner of chSPOP using co-immunoprecipitation (Co-IP) combined with liquid chromatography-tandem mass spectrometry methods. This interaction was further confirmed by fluorescence co-localization, Co-IP, and pull-down assays. It was interesting that exogenous recombinant protein HA-chSPOP or endogenous chSPOP alone was mainly located in the nucleus but was translocated to the cytoplasm upon co-expression with chMyD88 or lipopolysaccharide stimulation. In addition, chSPOP reduced chMyD88 expression by ubiquitination in a dose-dependent manner, and the regulation of NF-κB activity by chSPOP was dependent solely on chMyD88. Importantly, chSPOP played a negative regulatory role in the MyD88/NF-κB signaling pathway and the production of proinflammatory cytokines. Moreover, we found that velogenic Newcastle disease virus (NDV) infection changed the subcellular localization of chSPOP and the expression patterns of chSPOP and chMyD88, and overexpression of chSPOP decreased the production of proinflammatory cytokines to enhance velogenic and lentogenic NDV replication, while siRNA-mediated chSPOP knockdown obtained the opposite results, thereby indicating that chSPOP negatively regulated MyD88/NF-κB signaling pathway mediated proinflammatory cytokine production to promote NDV replication. These findings highlight the important role of the SPOP/MyD88/NF-κB signaling pathway in NDV replication and may provide insightful information about NDV pathogenesis.